Maggot Menageries: High School Student Contributions to Medicinal Maggot Production in Compromised Healthcare Settings. (16th December 2021) - Stadler, Frank; Arjona, Talia; Beaumont, Glenn; Bradley, Charlotte; Budd, Alyssa; Busana, Pedro; Clatworthy, Mathew; Fitz-Gibbon, Jodie; Goh, Kelvin G. K.; Hayes, Matt; Heather, Kylie; Lawton, Aisha; et al.
This case study describes how high school students can participate in research, development, and testing of real-life solutions for society's most intractable problems. In modern warfare, civilians make up most of the casualties, and conflict-affected communities are often isolated and have only limited access to healthcare. Most surviving casualties have limb wounds from injury or surgery, and many of these become infected and require long-term treatment or amputation. In 2020, MedMagLabs and the Queensland Virtual STEM Academy partnered to engage high school students to co-develop and test methods and training resources that empower people in conflict-affected communities to produce medicinal maggots for highly efficacious and affordable wound care. Maggot therapy is the treatment of wounds with living fly larvae to remove dead tissue, to control infection, and to promote wound healing. As opposed to most citizen science, which mainly focuses on data collection and/or educational and awareness-raising outcomes, this project focused on the co-creation of knowledge and the delivery of tangible research outcomes. The measure of its success was the development of end-user friendly medicinal maggot production methods and training resources. The study explains how citizen scientists and researchers collaborated with one another to achieve this objective. Project execution was largely in line with The Ten Principles of Citizen Science. Further review of project outcomes and self-reflection by the research team highlight important lessons for such collaborative studies, which have been summarised in five recommendations specifically relating to research collaborations with schools and student citizen scientists.